An Ethnobotanical Documentation Of Medicinal Plants Used By Local Communities Around Kibale National Park, A Case Of Kanyawara, Kanyansowera And Ibura Villages - Waisindye, Noah; Anywar, Godwin; Mugisha, Maud Kamatenesi; Kazibwe, Francis (International Journal of Advanced Information Science and Technology, 2016)
Currently there is rapid loss of traditional knowledge and practices due to their dependency on oral transformation, impacts of modern cultural transformation, and rapid land degradation. Ethno botanical documentation of medicinal plant use is generally an appropriate means of identifying potential sources of the new drugs. Research indicates that 74% of plant derived compounds used in pharmaceuticals, retained similar use as used by traditional healers. Motivation to study the conservation status of such medicinal plants can be realized if their local use is scientifically proven by first documenting them and testing them. Current study was carried out to document useful medicinal plants, that are becoming prone to threats of endangerment before scientific interventions are made, in the local communities of Kanyawara, Kanyansowera and Ibura adjacent to Kibale National Park (KNP), located 124km East of Ruwenzori foothills and 20km South East (SE) of Fort Portal Town in western Uganda, in Kabarole District. Data was collected using semi-structured interviews and guided questionnaires, house hold respondents were also chosen through random sampling. A total of 45 plant species from 28 families were recorded as useful medicinal plants harvested by people for managing diseases. Of the families encountered Asteraceae, Poaceae and Fabaceae had the highest number of species used followed by Bignoniaceae and Rutaceae. Though many plants have been used by the people in the study area to treat diseases, they have not been domesticated but are continuously being harvested from the wild. Such plants are prone to extinction yet could be domesticated for commercial purposes.